Qualitative sperm depletion: successive mating reduces initial sperm velocity in medaka fish - Yuki Kondo; Takeshi Ito; Satoshi Awata (Journal of Ethology, 2026)

Exploring particulate foraging as adaptive tactics amidst competitive grazing dynamics in Ryukyu-ayu Plecoglossus altivelis ryukyuensis - Kei’ichiro Iguchi; Shinji Takahashi; Hirokuni Goya; Satoshi Awata; Shin-ichiro Abe (Ichthyological Research, 2026)

Henpecked husbands: parental roles in the monogamous social fish Amphiprion clarkii depend on sex rather than relative size differences within pairs - Yuya Kobayashi; Chisaki Hosoda; Masanori Kohda; Satoshi Awata (Journal of Ethology, 2026)

Behavioral sequences during courtship and territorial defense of male Benthochromis horii in Lake Tanganyika - Ryoichi Inoue; Masaya Morita; Satoshi Awata; Shun Satoh (Hydrobiologia, 2025)

Punishment from dominant breeders increases helping effort of subordinates in a cooperatively breeding cichlid - Ryo Hidaka; Shumpei Sogawa; Masanori Kohda; Satoshi Awata (Animal Behaviour, 2024)

Sperm allocation in relation to male–male aggression and courtship in an externally fertilizing fish, the medaka - Yuki Kondo; Masanori Kohda; Yasunori Koya; Satoshi Awata (Animal Behaviour, 2023)

Tritiated water removal method based on hydrate formation using heavy water as co-precipitant - Satoshi Nakamura; Toshihiro Awata; Hitoshi Kiyokawa; Haruki Ito; Ryo Ohmura (Chemical Engineering Journal, 2023)

Correction to: Rhamphocottus nagaakii (Cottoidea: Rhamphocottidae), a new species of grunt sculpin from the northwestern Pacific, with notes on the phylogeography of the genus Rhamphocottus - Hiroyuki Munehara; Kouji Togashi; Sayuri Yamada; Takushi Higashimura; Aya Yamazaki; Shota Suzuki; Takuzo Abe; Satoshi Awata; Yasunori Koya; Osamu Tsuruoka (Ichthyological Research, 2022)

Rhamphocottus nagaakii (Cottoidea: Rhamphocottidae), a new species of grunt sculpin from the northwestern Pacific, with notes on the phylogeography of the genus Rhamphocottus - Hiroyuki Munehara; Kouji Togashi; Sayuri Yamada; Takushi Higashimura; Aya Yamazaki; Shota Suzuki; Takuzo Abe; Satoshi Awata; Yasunori Koya; Osamu Tsuruoka (Ichthyological Research, 2022)

Kin-structured cooperatively breeding groups due to limited dispersal in the obligate shell-brooding cichlid Neolamprologus meeli - Taiga Saeki; Shun Satoh; Joachim G. Frommen; Masanori Kohda; Satoshi Awata (Behavioral Ecology and Sociobiology, 2022)

The first record of egg masses in tunicates deposited by the snubnose sculpin, Orthonopias triacis , from the Northeastern Pacific: evidence for convergent evolution of an unusual reproductive strategy - Satoshi Awata; Takeshi Ito; Karen D. Crow; Yasunori Koya; Hiroyuki Munehara (Journal of Fish Biology, 2022)
In this study, the authors report the first record of egg masses deposited in solitary tunicates by the snubnose sculpin, Orthonopias triacis , from the Northeastern Pacific. Four egg masses were discovered in the tunicate Ascidia ceratodes that were genetically determined to be O. triacis . Female O. triacis had long ovipositors that allow deposition of their eggs inside the atrium of the tunicates. A comparison of host‐tunicate size with ovipositor length of sculpins from the Northwestern Pacific, including the genera Furcina and Pseudoblennius , revealed that O. triacis had shorter ovipositors and spawned in the atrium of smaller species of tunicates. Ancestral state reconstruction of egg deposition in solitary tunicates using 1.86Mbp RNAseq data of 20 sculpin species from Northeastern and Northwestern Pacific revealed that this unusual spawning behaviour may have evolved convergently in different species occurring in the Northeastern vs . the Northwestern Pacific.

Does construction in the spawning ground improve the riverbed conditions making it suitable for spawning of the Ryukyu-ayu Plecoglossus altivelis ryukyuensis? - Satoshi Awata; Tetsuya Tsuruta; Shin-ichiro Abe; Toshihiko Yonezawa; Kei’ichiro Iguchi (Ichthyological Research, 2020)

Host selection and ovipositor length in eight sympatric species of sculpins that deposit their eggs into tunicates or sponges - Satoshi Awata; Haruka Sasaki; Tomohito Goto; Yasunori Koya; Hirohiko Takeshima; Aya Yamazaki; Hiroyuki Munehara (Marine Biology, 2019)

Dynamics of sibling aggression of a cichlid fish in Lake Tanganyika - Shun Satoh; Kazutaka Ota; Satoshi Awata; Masanori Kohda (Hydrobiologia, 2019)

Optimal methods to fix fish sperm for optical microscopic observation: comparisons among different fixative solutions using sperms of copulatory and non-copulatory marine fishes - Takeshi Ito; Satoshi Awata (Ichthyological Research, 2019)

A Tanganyikan cichlid Neolamprologus mustax selectively exploits territories of another cichlid Variabilichromis moorii due to its inter-individual variation in aggression - Haruki Ochi; Satoshi Awata; Hiroki Hata; Masanori Kohda (Hydrobiologia, 2017)

Physiological characterization of anaerobic ammonium oxidizing bacterium ‘ C andidatus J ettenia caeni’ - Muhammad Ali; Mamoru Oshiki; Takanori Awata; Kazuo Isobe; Zenichiro Kimura; Hiroaki Yoshikawa; Daisuke Hira; Tomonori Kindaichi; Hisashi Satoh; Takao Fujii; Satoshi Okabe (Environmental Microbiology, 2015)
Summary To date, six candidate genera of anaerobic ammonium‐oxidizing (anammox) bacteria have been identified, and numerous studies have been conducted to understand their ecophysiology. In this study, we examined the physiological characteristics of an anammox bacterium in the genus ‘ C andidatus J ettenia’. Planctomycete KSU ‐1 was found to be a mesophilic (20–42.5°C) and neutrophilic ( pH 6.5–8.5) bacterium with a maximum growth rate of 0.0020 h −1 . Planctomycete KSU ‐1 cells showed typical physiological and structural features of anammox bacteria; i.e. 29 N 2 gas production by coupling of 15 NH 4 + and 14 NO 2 − , accumulation of hydrazine with the consumption of hydroxylamine and the presence of anammoxosome. In addition, the cells were capable of respiratory ammonification with oxidation of acetate. Notably, the cells contained menaquinone‐7 as a dominant respiratory quinone. Proteomic analysis was performed to examine underlying core metabolisms, and high expressions of hydrazine synthase, hydrazine dehydrogenase, hydroxylamine dehydrogenase, nitrite/nitrate oxidoreductase and carbon monoxide dehydrogenase/acetyl‐ CoA synthase were detected. These proteins require iron or copper as a metal cofactor, and both were dominant in planctomycete KSU ‐1 cells. On the basis of these experimental results, we proposed the name ‘ C a . J ettenia caeni’ sp. nov. for the bacterial clade of the planctomycete KSU ‐1.

Group composition, relatedness, and dispersal in the cooperatively breeding cichlid Neolamprologus obscurus - Hirokazu Tanaka; Dik Heg; Hirohiko Takeshima; Tomohiro Takeyama; Satoshi Awata; Mutsumi Nishida; Masanori Kohda (Behavioral Ecology and Sociobiology, 2015)

MicroRNA-33b downregulates the differentiation and development of porcine preadipocytes - Masaaki Taniguchi; Ikuyo Nakajima; Koichi Chikuni; Misaki Kojima; Takashi Awata; Satoshi Mikawa (Molecular Biology Reports, 2014)

Stress hormone responses in ayu Plecoglossus altivelis in reaction to different catching methods: comparisons between electrofishing and cast netting - Satoshi Awata; Tetsuya Tsuruta; Takashi Yada; Kei’ichiro Iguchi (Fisheries Science, 2013)

Seasonal changes in reproductive and physical condition, sexual dimorphism, and male mating tactics in the jewelled blenny Salarias fasciatus - Satoshi Awata; Saori Miura; Satoko Seki; Teppei Sagawa; Noriyosi Sato; Kazuhiko Sakai (Ichthyological Research, 2010)

Breeding season, spawning time, and description of spawning behaviour in the Japanese ornate dragonet, Callionymus ornatipinnis: a preliminary field study at the northern limit of its range - Satoshi Awata; Motoko R. Kimura; Noriyosi Sato; Keita Sakai; Takuzo Abe; Hiroyuki Munehara (Ichthyological Research, 2010)

Cooperatively breeding cichlid fish adjust their testis size but not sperm traits in relation to sperm competition risk - Satoshi Awata; Tomohiro Takeyama; Yoshimi Makino; Yuko Kitamura; Masanori Kohda (Behavioral Ecology and Sociobiology, 2008)

The effect of body size on mating system and parental roles in a biparental cichlid fish (Julidochromis transcriptus): a preliminary laboratory experiment - Satoshi Awata; Hideaki Takeuchi; Masanori Kohda (Journal of Ethology, 2006)

The effect of body size on mating system and parental roles in a biparental cichlid fish (Julidochromis transcriptus): a preliminary laboratory experiment - Satoshi Awata; Hideaki Takeuchi; Masanori Kohda (Journal of Ethology, 2006)

Structure and Polymorphism Analysis of Transforming Growth Factor Beta Receptor 1 (TGFBR1) in Pigs - Shin-ichi Shimanuki; Ayumi Mikawa; Yuko Miyake; Noriyuki Hamasima; Satoshi Mikawa; Takashi Awata (Biochemical Genetics, 2005)

Social system and reproduction of helpers in a cooperatively breeding cichlid fish (Julidochromis ornatus) in Lake Tanganyika: field observations and parentage analyses - Satoshi Awata; Hiroyuki Munehara; Masanori Kohda (Behavioral Ecology and Sociobiology, 2005)

Why egg-caring males of Isaza (Gymnogobius isaza, Gobiidae) refuse additional females: preliminary field observations - Daisuke Takahashi; Hatsuki Asada; Tomohiro Takeyama; Mizuki Takahata; Rei Katoh; Satoshi Awata; Masanori Kohda (Journal of Ethology, 2004)